2015
DOI: 10.1371/journal.pone.0142007
|View full text |Cite
|
Sign up to set email alerts
|

Human Genetic Relevance and Potent Antitumor Activity of Heat Shock Protein 90 Inhibition in Canine Lung Adenocarcinoma Cell Lines

Abstract: BackgroundIt has been an open question how similar human and canine lung cancers are. This has major implications in availability of human treatments for dogs and in establishing translational models to test new therapies in pet dogs. The prognosis for canine advanced lung cancer is poor and new treatments are needed. Heat shock protein 90 (HSP90) is an ATPase-dependent molecular chaperone ubiquitously expressed in eukaryotic cells. HSP90 is essential for posttranslational conformational maturation and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…IHC was performed using antibodies against pAkt Ser473 (phosphorylated Akt in Ser473, rabbit monoclonal antibody, diluted 1:50; Cell Signaling Technologies, Danvers, Massachusetts), pS6 Ser235/236 (phosphorylated S6 in Ser235/236, rabbit antibody, diluted 1:200; Cell Signaling Technologies, Danvers, Massachusetts) and Ki‐67 (mouse monoclonal anti‐human antibody, diluted 1:100; Dako, Carpinteria, California). All selected antibodies have been previously validated in dog tissues . Negative assay control included TMA slides processed for IHC on which the primary antibody was substituted for an isotype‐specific immunoglobulin (according to the primary antibody used: Rabbit (DA1E) mAb IgG XP Isotype Control; Cell Signaling Technologies or Mouse (G3A1) mAb IgG1 Isotype Control; Cell Signaling Technologies).…”
Section: Methodssupporting
confidence: 92%
“…IHC was performed using antibodies against pAkt Ser473 (phosphorylated Akt in Ser473, rabbit monoclonal antibody, diluted 1:50; Cell Signaling Technologies, Danvers, Massachusetts), pS6 Ser235/236 (phosphorylated S6 in Ser235/236, rabbit antibody, diluted 1:200; Cell Signaling Technologies, Danvers, Massachusetts) and Ki‐67 (mouse monoclonal anti‐human antibody, diluted 1:100; Dako, Carpinteria, California). All selected antibodies have been previously validated in dog tissues . Negative assay control included TMA slides processed for IHC on which the primary antibody was substituted for an isotype‐specific immunoglobulin (according to the primary antibody used: Rabbit (DA1E) mAb IgG XP Isotype Control; Cell Signaling Technologies or Mouse (G3A1) mAb IgG1 Isotype Control; Cell Signaling Technologies).…”
Section: Methodssupporting
confidence: 92%
“…None of these cell lines bore additional mutations in HER2. We have previously shown that BACA and CLAC do not contain HER2 amplification (by array comparative genomic hybridization) [34]. We next assessed HER2 activation in one HER2 V659E cPAC cell lines and three HER2 WT cell lines (two cPAC, papillary and unknown subtypes, and one cPASC) by…”
Section: Her2 Expression In Primary Canine Lung Cancermentioning
confidence: 99%
“…Canine/human comparative oncology—the study of analogous cancers in both humans and dogs—is playing increasingly important roles in advancing research in a variety of cancers, from both the basic science and clinical perspectives . Interspecies cancer studies have led to new insights into breast cancer, osteosarcoma, lung cancer and bladder cancer . Invasive bladder cancer in particular has become established as a model for comparative oncology due to the respective canine and human malignancies' similarities in environmental risk factors, tumor histology, tumor ploidy, sites of metastases, driver mutations, and modes of treatment .…”
Section: Introductionmentioning
confidence: 99%